Elevated EZH2 in ischemic heart disease epigenetically mediates suppression of NaV1.5 expression. (April 2021) - Zhao, Limei; You, Tao; Lu, Yan; Lin, Shin; Li, Faqian; Xu, Haodong
Abstract: Suppression of the cardiac sodium channel NaV 1.5 leads to fatal arrhythmias in ischemic heart disease (IHD). However, the transcriptional regulation of NaV 1.5 in cardiac ischemia is still unclear. Our studies are aimed to investigate the expression of enhancer of zeste homolog 2 (EZH2) in IHD and regulation of cardiac NaV 1.5 expression by EZH2. Human heart tissue was obtained from IHD and non-failing heart (NFH) patients; mouse heart tissue was obtained from the peri-infarct zone of hearts with myocardial infarction (MI) and hearts with a sham procedure. Protein and mRNA expression were measured by immunoblotting, immunostaining, and qRT-PCR. Protein-DNA binding and promoter activity were analyzed by ChIP-qPCR and luciferase assays, respectively. Na + channel activity was assessed by whole-cell patch clamp recordings. EZH2 and H3K27me3 were increased while NaV 1.5 expression was reduced in IHD hearts and in mouse MI hearts compared to the controls. Reduced NaV 1.5 and increased EZH2 mRNA levels were observed in mouse MI hearts. A selective EZH2 inhibitor, GSK126 decreased H3K27me3 and elevated NaV 1.5 in HL-1 cells. Silencing of EZH2 expression decreased H3K27me3 and increased NaV 1.5 in these cells. EZH2 and H3K27me3 were enriched in the promoter regions of Scn5a and were decreased by treatment with EZH2 siRNA. GSK126 inhibited the enrichment of H3K27me3 in the Scn5a promoter and enhanced Scn5a transcriptional activity. GSK126 significantly increased Na + channel activity. Taken together, EZH2 is increased in ischemic hearts and epigenetically suppresses Scn5a transcription by H3K27me3, leading to decreased NaV 1.5 expression and Na + channel activity underlying the pathogenesis of arrhythmias. Graphical abstract: Unlabelled Image Highlights: EZH2 and H3K27me3 are increased while NaV 1.5 expression is reduced in ischemic hearts. Silencing expression or suppressing activity of EZH2 leads to a decrease of H3K27me3 and an elevation of NaV 1.5. Suppressing activity of EZH2 enhances Scn5a promoter activity by decreasing H3K27me3. Suppressing activity of EZH2 increases Na + channel activity. EZH2-mediated suppression of NaV 1.5 is one of the mechanisms underlying arrhythmias in patients with IHD.